(untitled) (Italian Journal of Public Health, 2010)
The effectiveness of legislation and regulation as tools for injury prevention is well recognized in Europe. There is another tool that has been used effectively in the United States, but which is not substantially discussed in the European injury prevention literature. Litigation against the makers of unsafe products has been used in the US to create an incentive for manufacturers to invest in safer product design rather than risk a lawsuit and pay a penalty for neglect. This commentary discusses the use of litigation in the US as a tool for preventing injuries, and speculates on whether such an intervention might be feasible and desirable in Europe.